Complex Care Curriculum: Dysautonomia - Sonaly McClymont; Melanie Anspacher; Sarah Helen Evans; Neha Shah (Association of American Medical Colleges, 2013)
Abstract Introduction This resource was created to provide health care providers with educational materials related to care of the medically complex child with dysautonomia. Children with special health care needs (CSHCN) are increasingly prevalent in US hospitals. However, exposure to this patient population during training varies from provider to provider. No published educational curricula are specific to the inpatient care of this population. This resource is part of an educational curriculum for health care providers with the overall goal of improving inpatient care for this at-risk population. Methods This resource provides multimodal avenues for both individual self-study as well as small group teaching on the topic of dysautonomia in the medically complex child. Results This learning activity was first launched at Children's National Medical Center (CNMC) in Washington, DC in February 2012 as part of a curriculum designed to help providers manage medically complex children. Preliminary data from 15 out of 26 participants (58%) shows that 100% of participants agreed or strongly agreed to the following statements after viewing the self-learning module: (1) This learning activity met the stated learning objectives; (2) material presented in this learning activity was engaging and interesting; (3) material presented in this learning activity was relevant to my clinical practice; (4) material presented in this learning activity increased my comfort with teaching about this topic; and (5) format of this learning activity was appropriate for my learning needs. Eighty-seven percent of participants agreed or strongly agreed (the remaining 13% were neutral) to the statement "Material presented in this learning activity will change my clinical practice." Discussion Asynchronous learning modules can augment learning by providing individualized instruction and mastery of fundamentals. Based on this study, this module along with others in the curriculum continues to be offered to trainees and new faculty to augment their knowledge and skills in this area.